Refractory Gilles de la Tourette Syndrome—Many Pieces That Define the Puzzle - Szejko, Natalia; Lombroso, Adam; Bloch, Michael H.; Landeros-Weisenberger, Angeli; Leckman, James F. (Frontiers in Neurology, 2020)
Gilles de la Tourette syndrome (GTS) is a childhood onset neuropsychiatric disorder characterized by the presence of motor and vocal tics. The clinical spectrum of GTS is heterogenous and varies from mild cases that do not require any medical attention, to cases that are refractory to standard treatments. One of the unresolved issues is the definition of what constitutes treatment-refractory GTS. While for some other neuropsychiatric disorders, such as obsessive-compulsive disorder (OCD), a clear definition has been established, there is still no consensus with regard to GTS. One important issue is that many individuals with GTS also meet criteria for one or more other neurodevelopmental and neuropsychiatric disorders. In many individuals, the severity of these comorbid conditions contribute to the degree to which GTS is treatment refractory. The scope of this paper is to present the current state-of-the-art regarding refractory GTS and indicate possible approaches to define it. In closing, we discuss promising approaches to the treatment of individuals with refractory GTS.